Activated γδ T Cells With Higher CD107a Expression and Inflammatory Potential During Early Pregnancy in Patients With Recurrent Spontaneous Abortion - Yu, Long; Zhang, Yang; Xiong, Jinfeng; Liu, Jianjun; Zha, Ying; Kang, Qi; Zhi, Pan; Wang, Qiang; Wang, Hui; Zeng, Wanjiang; Huang, Yafei (Frontiers in Immunology, 2021)
Previous studies have reported the involvement of γδ T cells in recurrent spontaneous abortion (RSA), however, both pathogenic and protective effects were suggested. To interrogate the role of γδ T cells in RSA, peripheral blood from RSA patients and healthy women with or without pregnancy were analyzed for γδ T cells by flow cytometry (n=9~11 for each group). Moreover, the decidua from pregnant RSA patients and healthy controls (RSA-P and HC-P group, respectively) was simultaneously stained for γδ T cells by immunohistochemistry (IHC) and bulk sequenced for gene expression. Our results demonstrated that the frequencies of peripheral γδ T cells and their subpopulations in RSA patients were comparable to that in healthy subjects, but the PD1 expression on Vδ2+ cells was increased in pregnant patients. Furthermore, peripheral Vδ2+ cells in RSA-P patients demonstrated significantly increased expression of CD107a, as compared to that in pregnant healthy controls. In addition, RSA-P patients had higher proportion of IL-17A-secreting but not IL-4-secreting Vδ2+ cells compared to the control groups. In decidua, an inflammatory microenvironment was also evident in RSA-P patients, in which CCL8 expression and the infiltration of certain immune cells were higher than that in HC-P group, as revealed by transcriptional analysis. Finally, although the presence of γδ T cells in decidua could be detected during pregnancy in both RSA patients and healthy subjects by multicolor immunohistochemistry analysis, the expression of CD107a on γδ T cells was markedly higher in the RSA-P group. Collectively, our results indicated that the increased activation, cytotoxicity and inflammatory potential of peripheral and/or local γδ T cells might be responsible for the pathogenesis of RSA. These findings could provide a better understanding of the role of γδ T cells in RSA and shed light on novel treatment strategies by targeting γδ T cells for RSA patients.